1997
DOI: 10.1182/blood.v90.11.4369.4369_4369_4383
|View full text |Cite
|
Sign up to set email alerts
|

High Thrombopoietin Production by Hematopoietic Cells Induces a Fatal Myeloproliferative Syndrome in Mice

Abstract: To evaluate the effects of long-term, high-dose exposure to thrombopoietin (TPO), lethally irradiated mice were grafted with bone marrow cells infected with a retrovirus carrying the murine TPO cDNA. Mice were studied for 10 months after transplantation. In plasma, TPO levels were highly elevated (104 U/mL) throughout the course of the study. All mice developed a lethal myeloproliferative disorder evolving in two successive phases. During the first phase (7-9 weeks posttransplant), platelet and white blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 44 publications
8
77
0
Order By: Relevance
“…Likewise, inhibition of c‐Mpl‐dependent MK migration and function results in significantly decreased donor stem cell engraftment in murine transplantation assays (Olson et al , ). This is consistent with older data showing that TPO‐overexpressing mice develop a myeloproliferative phenotype similar to idiopathic myelofibrosis described in humans, with symptoms including thrombocytosis, leucocytosis and bone marrow myelofibrosis (Yan et al , ; Villeval et al , ). Together, these studies demonstrate that TPO not only drives proliferation and maturation of MKs but also other bone marrow‐derived progenitor cells.…”
Section: Thrombopoietinsupporting
confidence: 92%
“…Likewise, inhibition of c‐Mpl‐dependent MK migration and function results in significantly decreased donor stem cell engraftment in murine transplantation assays (Olson et al , ). This is consistent with older data showing that TPO‐overexpressing mice develop a myeloproliferative phenotype similar to idiopathic myelofibrosis described in humans, with symptoms including thrombocytosis, leucocytosis and bone marrow myelofibrosis (Yan et al , ; Villeval et al , ). Together, these studies demonstrate that TPO not only drives proliferation and maturation of MKs but also other bone marrow‐derived progenitor cells.…”
Section: Thrombopoietinsupporting
confidence: 92%
“…). We demonstrated that mice deficient in the MK transcription factor, GATA‐1, exhibit a profound increase in bone marrow MKs and exhibit a marked increase in osteoblast number and bone mass [Drachman et al, ; Villeval et al, ; Kacena et al, , , ]. Our current studies provide a potential Pyk2‐regulated mechanism for the MK‐mediated decrease in ALP.…”
Section: Discussionsupporting
confidence: 50%
“…Briefly, embryonic E13‐15 fetuses were dissected from pregnant WT mice, fetal livers were removed and single cell suspensions were generated. Cells were washed and then seeded in 100 ml culture dishes in Dulbecco modified eagle medium (DMEM) supplemented with 10% FCS and 1% murine thrombopoietin [Villeval et al, ]. MKs were isolated 5–7 days later by separating them from the lymphocytes and other cells using a one‐step albumin gradient to obtain a 90–95% pure MK population [Drachman et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Current dogma holds that bone marrow collagen fibrosis and osteosclerosis in the aforementioned conditions reflect a cytokine‐mediated secondary inflammatory response that is triggered by the abnormal interaction between clonal myeloid cells and polyclonal bone marrow stromal cells [2]. Various studies utilizing either tissue specimens from MPN patients or murine models that develop myelofibrosis have implicated either megakaryocytes/platelets [3–5] or monocyte/macrophage lineage cells [6, 7] as the key source for abnormal cytokine synthesis.…”
Section: Introductionmentioning
confidence: 99%